Dietary effects on inositol phosphate breakdown in the crop of broilers. Issue 1 (2nd January 2016) - Zeller, Ellen; Schollenberger, Margit; Kühn, Imke; Rodehutscord, Markus
ABSTRACT: The effect of diets differing in enzyme supplements, mineral phosphorus (P) and microwave wheat treatment on phytate hydrolysis and lower inositol phosphate isomers (InsPs) appearance in broiler crops was studied. The broilers (16- and 15-day-old) were assigned to 48 pens of 15 or 20 birds each ( n  = 8 pens per treatment) in Experiments 1 and 2, respectively. In Experiment 1, birds received a low-P wheat-soybean meal diet where the wheat was either microwave treated or not. These diets were offered without further supplementation or with added phytase (500 FTU/kg diet), alone or in combination with a xylanase (16, 000 BXU/kg diet). In Experiment 2, two maize-soybean meal-based diets were fed, without or with monocalcium phosphate supplementation. Furthermore, these diets were offered without further supplementation or with phytase at 500 or 12, 500 FTU/kg diet. On day 23 or 24 (Experiments 1 and 2, respectively), crop digesta were pooled per pen, freeze-dried and analysed for InsPs and the marker TiO2 . Microwaving reduced the intrinsic phytase activity and InsP6 hydrolysis, but increased the concentration of Ins(1, 2, 3, 4, 5)P5 and Ins(1, 2, 4, 5, 6)P5 in the digesta of crop (Experiment 1). Microwave treatment significantly interacted with enzyme supplementation for Ins(1, 2, 5, 6)P4 concentration, indicating a synergistic effect of intrinsic and supplied phytase in the crop. Xylanase tended to support phytase hydrolysis in diets with microwave-treated wheat. Phytase addition increased InsP6 hydrolysis up to 79% (Experiment 2). Thus, wheat phytase activity can cause high InsP6 hydrolysis in the crop. Treatment differences in lower InsPs indicated that hydrolysis of the first InsP6 phosphate group is not the only step in the degradation cascade in the crop of broilers that is influenced by dietary factors.